Post-operative effects of Oral Midazolam versus Hydroxyzine on Ketamine Intravenously Sedated children - Fallahinejad Ghajari, Masoud; Ansari, Ghassem; Bozorgmanesh, Anahita; Eghbali, Ahmad (Journal of Dental School, 2018)
Objectives The aim of this clinical trial was to compare the effects of oral Midazolam with oral Hydroxyzine on post sedation using IV Ketaminein children. Methods This single blind cross over clinical trial, was conducted on 25 children aged 2-6 years of ASA I and definitely negative by Frankl behavioral scale. Participants were divided into two groups: Group I received hydroxyzine syrup premed at the first session and midazolam oral at the 2nd visit. Group II received the premed in the opposite order. Vital signs, were recorded sedation depth, recovery and discharge status and compared potential adverse effects of sedative drugs were checked and recorded including sleepiness, nausea and vomiting, vertigo at 1stand 6th hours of discharge. Collected data were analyzed using SPSS V 20 using Repeated Measures ANOVA and Mann-Whitney tests. Results No significant differences were noticeable between two groups when vital signs, were compared in addition to response to drugs, working time, sleepiness, nausea and vomiting rates. However, there was a significant difference between groups in the incidence of vertigo one hour post operatively with higher prevalence in the Hydroxyzine group. (P=0.022) Conclusion Under the circumstances of this study, no significant difference was found between the two regimen groups, but vertigo was appeared as being higher after the first hour in the Hydroxyzine group.